A Comparative Photocatalytic Activity of ZnO and TiO₂ toward Rhodamine B Degradation under UV Irradiation - Uswatul Hasanah; Linda Jati Kusumawardani; Ani Iryani (Helium: Journal of Science and Applied Chemistry, 2026)
The rapid growth of Indonesia’s textile sector has increased waste output. Textile production generally uses synthetic dyes, such as rhodamine B. These manufactured substances typically contain compounds that are harmful to the environment. Photodegradation using photocatalysts is a common dye degradation method. Among various semiconductor materials, TiO₂ and ZnO are known to exhibit excellent photocatalytic activity. This study aims to assess the effectiveness of TiO₂ and ZnO photocatalysts in the degradation of rhodamine B dye. Several variables, including catalyst dosage (5, 15, 25, 35, 45, 55, 65, 75, and 85 mg), pH (4–8), and degradation time (60–480 min), were used to establish the photocatalytic process’s effectiveness and optimum conditions.The properties of TiO₂ and ZnO were characterized using scanning electron microscopy, X-ray diffraction, and BET analyses. Each catalyst (65 mg ZnO and 55 mg TiO₂) was added to the rhodamine B solution and exposed to a UV lamp to conduct the experiments. The results showed that TiO₂ demonstrated better photocatalytic efficiency than ZnO. The optimum degradation occurred after 6 h at pH 5. TiO₂ has a smaller crystal size and higher surface area than ZnO, contributing to its superior performance. The degradation efficiency reached 26.50% for ZnO and 48.40% for TiO₂. These data indicate that TiO₂ is more effective than ZnO for rhodamine B photodegradation under the examined conditions.